2017
DOI: 10.1051/e3sconf/20171901010
|View full text |Cite
|
Sign up to set email alerts
|

Sorption characteristic of coal as regards of gas mixtures emitted in the process of the self-heating of coal

Abstract: Abstract. One of the most challenging tasks in the coal mining sector is the detection of endogenous fire risks. Under field conditions, the distance between the points where samples for the analyses are collected and the actual place where coal self-heating takes place may be quite remote. Coal is a natural sorbent with a diverse character of pore structures which are surrounded by fractures and cleavage planes constituting ideal spaces for the flow and adsorption of gases. The gases (methane, ethane, ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Similar results ( Fig. 3) are obtained by processing other experimental data [19][20][21][22][23][24][25][26]. This indicates a different transformative effect of pressure, temperature, and time factors at individual stages of metamorphism.…”
Section: Research Results and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results ( Fig. 3) are obtained by processing other experimental data [19][20][21][22][23][24][25][26]. This indicates a different transformative effect of pressure, temperature, and time factors at individual stages of metamorphism.…”
Section: Research Results and Discussionsupporting
confidence: 85%
“…1, c). TECHNOLOGY [19][20][21][22][23][24][25][26]: а -the ratio between the carbon content and a mixture of other components (О 0 , Н 0 , N 0 ); b -the ratio between the content of carbon and oxygen; c -the ratio between the content of carbon and hydrogen; d -the ratio between the carbon content and nitrogen; I, II, III, IV -ranges of changes in the properties of coal; 1 -linear interpolation of experimental data; 2 -the boundaries of the change in components; • -experimental data…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Figure 3a-c,e represents the values at the outlet of the sorption column at the temperatures of 323 K, 373 K, 423 K, 473 K and 523 K, respectively. In the case of samples with number 1-9, the sorption indices were calculated based on the results obtained and published in earlier papers [20][21][22], but in this study these results were used in the context of the sorption index (SG). Based on the results drawn for individual samples at the inlet of the sorption column, it was established that the sorption indices of combustion products attained mostly have a value below 3.…”
Section: Resultsmentioning
confidence: 99%
“…The gas can originate from sources other than the self-heating process, i.e., natural content, acid mine water neutralization, machines with diesel-fueled engines working underground or the injection of carbon dioxide into a sealed area as an inert gas [24,32]. Additionally, studies on the fire gases sorption on coal also showed that carbon dioxide is easily absorbed on coal surface due to its small kinetic diameter (0.33 mm), a linear structure and a high quadruple moment of molecules [28,33,34]. This phenomenon may result in underestimating the value of the gas concentration at the monitoring station, especially when the distance between the source of fire and the sampling point is long.…”
Section: Gases Emission Profilementioning
confidence: 99%